Application Of Weight Sum Model (WSM) In Determining Special Allocation Funds Recipients - Dikki Handoko; Mesran Mesran; Surya Darma Nasution; Yuhandri Yuhandri; Heri Nurdiyanto (STMIK Budi Darma, 2017)
In the management of education is not uncommon educational institutions sometimes receive sources of funds from outside, one of which comes from the Department of Education in the implementation of its duty to provide one allocation of funds called Special Allocation Fund (DAK). This assistance is from APBN revenues to areas devoted to schools to help fund special activities such as the addition or improvement of school facilities and infrastructure. The application of this special allocation grantee needs to use a Decision Support System (CMS) to allow decisions to be generated in favor of the DAK beneficiary. In the application of SPK required MCDM method, the Weight Sum Model (WSM), which is a simple method and able to generate ranking from the proposer alternatives in a special allocation fund.